2008
DOI: 10.1038/sj.bjc.6604704
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of testicular microlithiasis in men with familial testicular cancer and their relatives

Abstract: Testicular germ cell tumours (TGCT) cluster in families, but responsible genes remain unidentified. The association between testicular microlithiasis (TM) and testicular carcinoma in situ (CIS) suggests that TM may be a TC risk factor. We report testicular ultrasound findings in men with familial TGCT (FTGCT) and their unaffected relatives. A total of 81 men (48 affected and 33 unaffected) from 31 families with X2 TC cases underwent testicular ultrasound. Testicular microlithiasis was defined as either 'classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Male infertility also confers a significantly increased risk of testicular cancer (Standardized Incidence Ratio [SIR] 2.8, 95%CI=1.5–4.8) (33). Both our group and British investigators have implicated testicular microlithiasis in TGCT risk (34, 35). There is also evidence that infertility may be increased in males from TGCT families compared with the general population (36).…”
Section: Introductionmentioning
confidence: 86%
“…Male infertility also confers a significantly increased risk of testicular cancer (Standardized Incidence Ratio [SIR] 2.8, 95%CI=1.5–4.8) (33). Both our group and British investigators have implicated testicular microlithiasis in TGCT risk (34, 35). There is also evidence that infertility may be increased in males from TGCT families compared with the general population (36).…”
Section: Introductionmentioning
confidence: 86%
“…There are important aetiologic implications if it can be established that single nucleotide polymorphism (SNP) associations are homogenous in familial and sporadic cases. The National Cancer Institute's (NCI) Clinical Genetics Branch is conducting a multidisciplinary aetiologic study of familial and sporadic bilateral TGCT, and those cases are independent of those published in GWAS to date 14. Here, we investigated whether four of the previously identified regions are associated with familial or bilateral TGCT cases in our study cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a genetic predisposition has been suggested for human testicular microlithiasis (ie, microcalcification within seminiferous tubules). 45,46 In clinical studies of humans, testicular microlithiasis has been detected in several pathological conditions, including infertility, cryptorchidism, testicular neoplasms, Klinefelter's syndrome, varicocele, and torsion of the testis, 47,48 as well as in normal testes. 45,49 Whether scrotal hyperthermia can induce irreversible calcification in human testes is unclear, but it has been reported that scrotal hyperthermia by exposure to sauna heat could have adverse effects on human spermatogenesis over 3 months.…”
Section: Heat-induced Testicular Calcificationmentioning
confidence: 99%